The Legacy of Past Tree Planting Decisions for a City Confronting Emerald Ash Borer (Agrilus planipennis) Invasion - Greene, Christopher S.; Millward, Andrew A. (Frontiers in Ecology and Evolution, 2016)
Management decisions grounded in ecological understanding are essential to the maintenance of a healthy urban forest. Decisions about where and what tree species to plant have both short and long-term consequences for the future function and resilience of city trees. Through the construction of a theoretical damage index, this study examines the legacy effects of a street tree planting program in a densely populated North American city confronting an invasion of emerald ash borer (Agrilus planipennis). An investigation of spatial autocorrelation for locations of high damage potential across the City of Toronto, Canada was then conducted using Getis-Ord Gi*. Significant spatial clustering of high damage index values affirmed that past urban tree planting practices placing little emphasis on species diversity have created time-lagged consequences of enhanced vulnerability of trees to insect pests. Such consequences are observed at the geographically local scale, but can easily cascade to become multi-scalar in their spatial extent. The theoretical damage potential index developed in this study provides a framework for contextualizing historical urban tree planting decisions where analysis of damage index values for Toronto reinforces the importance of urban forest management that prioritizes proactive tree planting strategies that consider species diversity in the context of planting location.